D3 Visualization LiveLessons (Sneak Peek Video Training) : An Introduction to Data Visualization in JavaScript - King, Ritchie S.; Safari eBooks ([Place of publication not identified] : Addison-Wesley Professional, 2014)
"In this video training, the presenter starts by introducing D3: the beautiful interactive data visualizations it's capable of creating, the reasons why it's such a powerful library, and how to start using it. They then take a brief, but necessary, detour to introduce Scalable Vector Graphics (SVG)-a standard for rendering graphical elements on the web that D3 works particularly well with. From there, they walk through how to construct an interactive bar chart, rendered in SVG, but built entirely with D3, starting with very basic D3 concepts and adding more and more sophistication, lesson by lesson. Finally, they cover how to strike out on your own. After watching this video, designers and developers will feel comfortable diving right in to D3 and telling elegant visual stories with web graphics."--Resource description page.
Title from resource description page (viewed November 17, 2014).
Presenter, Ritchie S. King.
Keywords: Interactive computer graphics; JavaScript (Computer program language); Electronic books